FEKTIVITAS BIMBINGAN PERKAWINAN DI KANTOR URUSAN AGAMA KECAMATAN SIPISPIS KABUPATEN SERDANG BEDAGAI DALAM MEMBANGUN KELUARGA SAKINAH DALAM PERSPEKTIF HUKUM ISLAM - Ramadhan Syahmedi Siregar, Julhaidir Purba, Nispul Khairi, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstract: The background of this research is less of civil desire to entire the family. KUA and BP4 to keep strong forward for family to go for sakinah. The purpose of this research is to find out how is the effectiveness of marriage council at the sub-regency in building happy plan family in Islamic law study. This research was used the qualitative method. This research was placed at the sub-regency of Sipispis. The data collecting technique used the documentation, the interview and observation. Data analysis technique used data reduction, servicing data and the conclusion. The source of data used is primary source and secondary source. The result of research showed the using of plan and applying of BP4 and KUA in building the communities' realization toward the happy plan family at the sub-regency of Sipispis had contained of two sections, external and internal. The side of external those are; (a) several couple of their happy plan family gathering is too low, (b) several couple of their economic level is too low, and (c) several couple of their economic level is too middle. And the side of internal those are; (a) the position and status of BP4 and KUA had constructed by fund of APBN and APBD was not going to be well done, (b) the job description and the function applying were not going to be well done global, (c) the managerial' s staff ability wasn't going to be well done, (d) the globalization development and the integrity effected the information technology and brought the influence for the societies' living and the life style such as hedonism, materialistic, and consumerism that challenge the religious' value. The side of support those are; (1) the biggest hopefully and the societies' support to build the happy plan family, (2) the strongest of the government for BP4 to create the family's happy plan going to an eternal position based on the one pillar of Pancasila and based on the marriage's purposes as it was declared by the law of number 1 year 1974 about the marriage and Islamic law compilationKeywords; Effectiveness, Marriage Guidance, Sakinah Family